Home dental care during the Covid-19 pandemic: literature review (Research, Society and Development, 2022)
SARS-CoV-2 or new corona virus was first identified in China at the end of 2019 and has taken on worldwide proportions. Dentistry professionals emerge as a category exposed to a high risk of contamination in the work environment, due to rotating instrumentation and direct action in the oral environment. In this context, home care represents an efficient form of health care, especially for systemically compromised patients. Analyzing the importance of home dental treatment and its challenges in the face of the Covid-19 pandemic, the present study aims to carry out a literature review in order to inform and discuss about dental home care services in the midst of the pandemic period. The final research to discuss the steps of the guideline discussed here resulted in 15 articles. The practice of home care grew in Brazil in the years of the pandemic and through preventive actions, it offers the performance of several procedures. Home assistance emerges as an option for the promotion and maintenance of patients' health. In view of the findings obtained, it is concluded that home dental care has become more frequent during the Covid-19 pandemic, having as one of its principles the integrality with the other specialties to provide an excellent treatment to the patient, based on good practices. biosecurity practices. Therefore, it is proven that home dental care is an important type of assistance, and must be performed with due care, to guarantee more safety.